INVESTIGATING PROSPECTIVE TEACHERS’ MATHEMATICAL KNOWLEDGE FOR TEACHING IN QUADRILATERAL OF SKILL DIFFERENCES - latief sahidin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Mathematical knowledge for teaching (MKT) is one of the factors that affect the competence of prospective teachers in learning. This study aims to describe the MKT of prospective teachers in terms of differences in ability levels in the scope of quadrilateral. The MKT studied in this study includes common content knowledge, and knowledge of the mathematical horizon. The research subjects consisted of three prospective math teachers, namely high-skill, intermediate-skill and low-skill. This research is qualitative research using vignettes. Data in this study was collected through vignettes and interviews. Validity of data using time triangulation. The results of this study showed that the ability of prospective teachers of intermediate-skilled and low-skill teachers still have difficulty regarding quadrilateral convex and quadrilateral concaves and still have difficulty understanding the relationships of squares, rectangles, rhombus and parallelogram. The MKT of intermediate and low-skill subjects of being produced is still limited compared to high-skill subjects. This difference occurs because it has not been able to eliminate the rectangular prototype image. To develop their abilities, prospective teachers need to be equipped with quadrilateral exploration tasks in education and training.